Modernization and Intensification of Nitric Acid Plants - Wilk, Marcin; Kruszewski, Andrzej; Potempa, Marcin; Jancewicz, Romuald; Mendelewski, Jacek; Sławiński, Paweł; Inger, Marek; Nieścioruk, Jan (IntechOpen, 2012)
None